FACTORS AFFECTING SLEEP DISORDERS OF PATIENTS IN THE INTENSIVE CARE UNIT (ICU) - Hadi, Hadi (Proceedings of the International Conference on Applied Science and Health, 2017)
Introduction: There is a tendency for cardiac patients in the intensive care unit (ICU)âs bed to be more disturbed than when they are still at home. The cause of the sleep disorder among these patients are allegedly caused by many factors, including environmental influences such as noise and lighting and also nursing interventions among other reasons. Objective: To investigate the relationship between sleeping disorders and environmental factors, namely noise and lighting, and nursing interventions. Methods: The design used in this research is descriptive analysis with cross sectional approach. The sampling technique is purposive sampling with the sample size of 30 respondents. The analysis of the data is used to determine the frequency distribution and relationships among variables causes of sleeping disorders among cardiac patients in ICU. Results: The results showed that most respondentsâ sleep is disrupted (60.0%) and interrupted once (40.0%) with the details of each sleeping disturbance factor are as follows: from the noise is disturbed (53.3%) and interrupted once (20.0%), from the lighting is disturbed (40.0%) and interrupted once (33.3%), and from nursing interventions is disturbed (43.3%) and interrupted once (10.0%). Conclusion: In providing nursing care, nurses need to pay attention to factors that affect sleeping disorders among heart patients in the ICU.Â